The Role of Interpersonal Communication in Improving Student Interaction Skills in Elementary Schools - Namiroh Lubis; Maemonah Maemonah (Lembaga Yasin AlSys, 2025)
This study critically examines the role of social communication in enhancing interaction skills among elementary school students, with a specific focus on SD IT Al-Munawwar. Elementary education serves as a vital stage for cultivating social competencies that support meaningful engagement both within and beyond the classroom. Drawing on Durkheim’s theory of social solidarity, the study explores how structured social communication fosters a collaborative and inclusive learning environment. Employing a qualitative research approach, the study involved homeroom teachers and students as participants. The findings indicate that implementing social communication strategies, such as group discussions, interactive learning activities, and creative pedagogical approaches significantly improves students’ ability to interact effectively. Additionally, the study highlights the growing influence of digital platforms on student interactions, emphasizing the need to optimize communication strategies in response to the evolving educational landscape. These insights offer practical recommendations for educators, particularly at SD IT Al-Munawwar, in designing responsive and effective learning methods that address the communication needs of students in the digital era.